2004
DOI: 10.2337/diabetes.53.2007.s31
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in the Proximal Promoter Region of the Adiponectin (APM1) Gene Are Associated With Type 2 Diabetes in Swedish Caucasians

Abstract: Adiponectin (APM1) is an adipocyte-derived peptide.The APM1 gene is located on chromosome 3q27 and linked to type 2 diabetes. In patients with type 2 diabetes, the adiponectin level in plasma is decreased in comparison to healthy subjects. To identify genetic defects of the APM1 gene that contribute to the development of type 2 diabetes, we genotyped 13 single nucleotide polymorphisms (SNPs) in 106 patients with type 2 diabetes, 325 patients with impaired glucose tolerance (IGT), and 497 nondiabetic control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
104
4
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 22 publications
(32 reference statements)
10
104
4
9
Order By: Relevance
“…For the other SNPs studied, we found no association with hyperglycaemia, in contrast to previous reports on SNPs A-11426G [9], C-11377G [8,9] and G276T [7,11]. This may again be explained by differences in ethnicity and study design.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For the other SNPs studied, we found no association with hyperglycaemia, in contrast to previous reports on SNPs A-11426G [9], C-11377G [8,9] and G276T [7,11]. This may again be explained by differences in ethnicity and study design.…”
Section: Discussioncontrasting
confidence: 99%
“…An increased risk of diabetes mellitus was shown in subjects with the GG genotype (OR=1.70) in a Japanese population [7], and the G allele was also associated with reduced insulin sensitivity and increased BMI in a German cohort [10]. However, another group found that the T allele contributed to the risk of hyperglycaemia [11], and others failed to find any association of the T45G polymorphism with diabetes mellitus in Europids [8,9,18] and Pima Indians [19]. Most of the conflicting results among reported case-control studies could have been caused by statistical fluctuations, such as sampling errors related to small sample sizes, and reporting biases consequent to inadequate allowance for type 1 error and multiple testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study on Italians by Nannipieri et al [17], French population based study by Vasseur F et al [18] and Gu et al [19] study report on Swedish subjects also showed no association among SNP45 T [ G of adiponectin gene and insulin resistance. This may be due to variation in the ethnic group.…”
Section: Discussionmentioning
confidence: 93%
“…9 Variations in the adiponectin gene (APM1) have been associated with type 2 diabetes in many populations. [10][11][12][13][14][15][16] The adiponectin gene has thus emerged as a susceptibility gene for type 2 diabetes, as well as for cardiovascular disease and obesity. The intronic G276T variant, located in intron 2, is one of the most extensively studied variants within the adiponectin gene and has the most consistent published results.…”
Section: Introductionmentioning
confidence: 99%